Ionospheric disturbances associated with the eruption of Mt. Asama observed by TEC data and HF Doppler sounding - Hiroyuki Nakata; Aritsugu Chonan; Keisuke Hosokawa; Takuya Tsugawa; Michi Nishioka; Hiroyo Ohya (Earth, Planets and Space)
Abstract Mt. Asama, Nagano Prefecture, Japan, erupted at 11:02 UT on September 1st, 2004. Ionospheric disturbances associated with this eruption were detected using TEC data and HF Doppler observations. It has already been reported that the TEC data obtained from GNSS receivers revealed that N-shaped disturbances in TEC with a period of 76 s occurred 12 min after the eruption. In the HF Doppler sounding observations, on the other hand, a spiky variation in the Doppler frequency with a frequency of about 10 mHz was observed 9–11 min after the eruption. Ray tracing calculations of the acoustic waves confirmed that both N-shaped disturbances in TEC and the spiky variations in the Doppler frequency were generated by the acoustic wave due to the eruption of Mt. Asama. Compared to earthquakes, volcanic eruptions are treated as point sources of atmospheric waves. Therefore, the acoustic waves produced by the present eruption were considered to behave as shock waves. In the HF Doppler observation, subsequent to the spiky signature, a longer-period wavy disturbance appeared. The frequency of these long-period disturbances is about 4 mHz, which is almost the same as the coseismic ionospheric disturbances. The cause of these long-period disturbances is considered to be gravity waves due to the partial transformation of the eruption energy or the acoustic resonance between the ground and lower ionosphere. Although both are typical causes of disturbance associated with earthquakes, it was difficult to determine which was the primary cause in the present case. In order to clarify the cause of wavy disturbances in the present event, it is necessary to investigate atmospheric waves associated with volcanic eruptions in detail using additional observation data, such as ground-based infrastructure sound networks. Graphical Abstract